2021
DOI: 10.1039/d0lc01012j
|View full text |Cite
|
Sign up to set email alerts
|

Microliter ultrafast centrifuge platform for size-based particle and cell separation and extraction using novel omnidirectional spiral surface acoustic waves

Abstract: Acoustically centrifuge and extract cells from blood samples using 152-Y-rotated lithium niobate and spiral electrodes with an extraction syringe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 40 publications
1
31
0
Order By: Relevance
“…On the other side, surface acoustic wave (SAW) actuators have been extensively studied for manipulation of liquid particularly with volumes of microlitres or even smaller [37][38][39] . SAW devices are commonly composed of interdigitated electrodes that are patterned on a piezoelectric substrate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other side, surface acoustic wave (SAW) actuators have been extensively studied for manipulation of liquid particularly with volumes of microlitres or even smaller [37][38][39] . SAW devices are commonly composed of interdigitated electrodes that are patterned on a piezoelectric substrate.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, surface acoustic wave (SAW) actuators have been extensively studied for the manipulation of liquids particularly with volumes of microlitres or even smaller. [37][38][39] SAW devices are commonly composed of interdigitated electrodes that are patterned on a piezoelectric substrate. They have been widely used in acoustofluidics to manipulate droplets for sample preparation, sorting, patterning, mixing, pumping, jetting, and nebulisation.…”
Section: Introductionmentioning
confidence: 99%
“…Surface acoustic waves in the frequency range of 10's MHz to 10's GHz [150,[197][198][199][200][201] have gained increased attention due to their extensive value in manipulation, separation, and concentration of organisms, [202][203][204] cells, [205][206][207][208][209][210][211][212][213][214][215][216][217][218] particles, [140,212,215,[219][220][221][222][223][224][225][226][227][228][229] and nanomaterials. [230][231][232] Recently, surface acoustic waves have been leveraged to develop various technologies for sonoporation.…”
Section: High-frequency Surface Acoustic Wave-based Technologiesmentioning
confidence: 99%
“…Shilton et al 32 proposed to enrich particles using focused SAWs rapidly. Instead of straight IDTs, Zhang et al 33 designed an omnidirectional spiral SAW device and achieved particle enrichment utilizing the induced planar recirculating acoustic streaming in a droplet. Gu et al 20 demonstrated the enrichment and separation of nanoparticles in 1 min using the entanglement of the SAW actuation and spinning droplet.…”
Section: Introductionmentioning
confidence: 99%